Research Status of SARS-CoV-2 on Cardiovascular System Injury in Children - Zhang,Yuhai (2021)
Abstract In December 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) began to break out in the Hubei Province of China. At present, the epidemic situation in the world continues and the number of confirmed cases is increasing every day. A recent review showed that children under the age of ten years make up about 1% of the infected population, which cannot be ignored. Studies have shown that after SARS-CoV-2 infection children can show clinical symptoms of cardiovascular system damage in addition to typical respiratory symptoms. This article mainly discusses the possible damage of SARS-CoV-2 to children's cardiovascular system and related mechanisms.